DINAMIKA KONFLIK SUNNI-SYIAH DI INDONESIA PRESPEKTIF KUASA MICHEL FOUCAULT - Sultriana, Sultriana; Mustahyun, Mustahyun (IAIN Palopo, 2017)
Sunnis and Syiâah are two mazhab (Islamic schools ) that often argue in some aspects such as the perspective of the khilafah. Sunni is the majority in Indonesia. It naturally has ego power to do injustice such as pressing and even attacking which Sunni thinks disagree on what Sunniâs members believe, because according to them, their belief is something right. With that understanding, those who are opposed to their counterparts in this case Syiah as a minority will be cornered and even intimidated by the Sunniâs majority. In view of the problem, the writer used Michel Foucaults analysis of his theory of